The bad seed [videorecording (DVD)] - Mahin, John Lee, 1902-1984; Kelly, Nancy, 1921-1995; McCormack, Patty, 1945-; Jones, Henry, 1912-1999; Heckart, Eileen, 1919-2001; Varden, Evelyn, 1893-1958; Hopper, William, 1915-1970; Rosson, Harold, 1895-1988; Hurst, Ralph; Mabry, Moss; North, Alex; Anderson, Maxwell, 1888-1959 (Warner Bros. Entertainment, 2004)
A mother makes the tortuous discovery that her cherubic eight year old daughter harbors an innate desire to kill.